The overhead squat - Jones, Z. S.; Matos, N. D.; Piper, T. J. (Journal of Australian Strength and Conditioning, 2020)
The overhead squat has many applications for the strength and conditioning coach. It is an effective way to improve snatch technique, helps to reveal common issues with mobility, and, with proper corrections, can make the coaches job easier. The purpose of this paper is to explain the basic steps of the overhead squat and how to use the exercise within a strength and conditioning program. Success and safety of the snatch exercise requires the ability to achieve the prerequisite positions exhibited during the overhead squat. The instruction and cues for teaching beginners how to overhead squat are included. How to safely and properly "miss" or drop the barbell limits the risk of injury typically related to mobility issues. Common coaching cues and corrections are presented to help the coach become more effective at improving overhead squat technique. Errors in the overhead squat include the heels coming off the floor, the bar sitting to far behind the athlete, shrugged shoulders, and bent elbows. Cues that can encourage proper movement include, "sit back" to help keep the heels down, "stretch the bar" to keep the bar in position, "squeeze your scaps" to avoid shrugged shoulders, and "punch out" to avoid bent elbows and shoulder internal rotation. Overhead squats have been shown to be useful in detecting potential mobility issues in the shoulder complex, trunk, ankles, and as part of the Functional Movement Screen. For the strength coach the overhead squat can be used as an effective instructional sequence for the snatch, as a squat variation used in training programs, or as a mobility assessment. Technique, properly missing, and common errors and cues are outlined in the video.